Managerial measures to reduce rework and improve construction safety in a developing country: Malaysian case - Yap, Jeffrey Boon Hui; Skitmore, Martin; Chong, Jia Rou; Hon, Carol K. H. (Journal of Civil Engineering and Management, 2022)
Previous studies demonstrate that rework can lead to more safety incidents. However, there is an inadequate understanding of how construction rework reduction measures may significantly decrease the likelihood of safety incidents in developing countries. To explore how construction organisations can integrate rework minimisation and safety management in practice, this study examines the effectiveness of the management strategies that can reduce rework and improve safety. Based on a two-stage detailed literature review of both rework- and safety-related studies, 13 managerial measures are recognised that are capable of jointly reducing rework and safety incidents for construction projects. A field survey involving construction professionals in Malaysia was used to analyse and rank these measures according to effectiveness indices for rework, safety and joint rework-safety management. Factor analysis yielded a two-factor solution comprising (1) project management best practices and (2) proactive competency management. It is suggested that the construction industry would benefit from simultaneously ameliorating the quality and safety performance of projects by adopting effective joint measures that are predominantly guided by process (best practices) and people (competency management) components.